The Development Of Project-Based Islamic Cultural History Learning Materials On Ali Ibn Abi Talib’s Exemplary Character To Strengthen Generosity And Love Values In Fifth-Grade Madrasah Ibtidaiyah Students - Siti Fauziah; Mardhiya Agustina (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
Background: Islamic Cultural History (SKI) learning in Madrasah Ibtidaiyah is often focused on cognitive understanding and provides limited opportunities for students to practice character values in real-life situations. Consequently, the value of generosity exemplified by Ali bin Abi Talib has not been optimally internalized by students. Objective: This study aimed to develop and evaluate the feasibility, practicality, and effectiveness of Project-Based Learning (PjBL)-based SKI instructional materials integrated with CINTA values to foster generosity among fifth-grade Madrasah Ibtidaiyah students. Method: This study employed a Research and Development (R&D) approach using the ADDIE model, consisting of Analysis, Design, Development, Implementation, and Evaluation stages. The participants were fifth-grade students of MIN 6 Tapin. Data were collected through observations, interviews, questionnaires, documentation, learning achievement tests, project assessments, and attitude observations. Data were analyzed using descriptive qualitative and quantitative techniques. Results: The developed product achieved a very high level of validity with an average expert validation score of 84.55%, was highly practical based on teacher assessments (92.1%), and received highly positive student responses (93.3%). The implementation process was rated excellent with a score of 92.9%. Learning outcomes improved from a pretest mean score of 67.4 to a posttest mean score of 88.6, while students’ generosity attitudes increased from 70.8% to 92.4%. Novelty: This study integrates the CINTA values framework into PjBL-based SKI instructional materials focusing on the exemplary character of Ali bin Abi Talib, providing a systematic approach to character education through authentic learning experiences. Conclusion: The developed instructional materials are valid, practical, and effective in enhancing students’ understanding of Islamic historical figures while fostering generosity and character development through meaningful project-based learning activities.